Communication Patterns in Efforts to Improve Employee Performance in Human Resource and Personnel Development Agency - Nurwati, Nurwati; Djalil, Nur Alim; Akbar, Muh. (Journal of Management and Administration Provision, 2024)
This study aims to determine how communication patterns in the Human Resources Development Staffing Agency of Penajam Paser Utara Regency where the communication pattern itself is a very important part in conveying information from a leader to his subordinates, which includes a source of information, as a memory center for the organization and the creation of ideas or ideas in order to achieve the desired goals of the company or agency. This research also focuses on four communication patterns, namely primary, secondary, linear, and circular communication patterns. The results showed that the government officials at the Human Resources Development Staffing Agency of Penajam Paser Utara Regency were quite capable of using secondary, linear, and circular communication patterns in their daily communication processes, but in using primary communication patterns there was an imbalance between the use of verbal and nonverbal symbols in it, so that it makes the communication process that occurs less effective, and this will also affect the level of performance in the Personnel and Human Resources Development Agency of North Penajam Paser Regency, because if the communication patterns carried out can run well, it will make the performance at the Personnel and Human Resources Development Agency of North Penajam Paser Regency be maximized and as expected.